2021
DOI: 10.7759/cureus.15974
|View full text |Cite
|
Sign up to set email alerts
|

Parrot Beak Nail: Case Report and Review of Parrot Beak Nail Dystrophy

Abstract: Parrot beak nail dystrophy is an excessive forward curvature of the nail plate that can affect both fingernails and toenails. Few cases have been reported since its original description in 1971; however, the incidence is estimated to be 2.5% in healthy individuals. Although the pathogenesis has not yet been established, parrot beak nail has been associated with chronic crack cocaine use, congenital bone or soft tissue abnormalities, other nail dystrophies, peripheral neuropathy, systemic sclerosis, and trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“… 1 Authors who support this theory claim the over curvature seen in PBN can be temporarily corrected after submerging the affected nail in water for some minutes, since it would overcome those hydrophobic interactions. 2 An injury could be the main cause, as in the present study’s second and third cases. It would generate a chronic imbalance of growth and alter the content of hydrophobic phospholipids, leading to a pronounced longitudinal curvature.…”
mentioning
confidence: 49%
See 3 more Smart Citations
“… 1 Authors who support this theory claim the over curvature seen in PBN can be temporarily corrected after submerging the affected nail in water for some minutes, since it would overcome those hydrophobic interactions. 2 An injury could be the main cause, as in the present study’s second and third cases. It would generate a chronic imbalance of growth and alter the content of hydrophobic phospholipids, leading to a pronounced longitudinal curvature.…”
mentioning
confidence: 49%
“…Other case series have shown that 31% of patients with systemic sclerosis can present this nail dystrophy. 2 , 3 This deformity has been found in 11 to 89-year-old patients, without sex predominance. We found nine articles reporting this clinical finding, with a total of 78 patients ( Table 1 ).…”
mentioning
confidence: 93%
See 2 more Smart Citations